The Suitability of Green Open Space in Mijen District Based on PERDA Kota Semarang Nomor 7 Tahun 2010 - Hana Sugiastu Firdaus; Fauzi Janu Ammarohman; Andrie Tri Nur Cahyanto (Journal of Applied Geospatial Information, 2022)
The physical development phenomenon of a city in Indonesia causes significant changes in the land-use system. One of the impacts is the reduction in Green Open Space (RTH), which also occurs in Mijen District, Semarang City. In 2010, the Semarang City Government ratified Regional Regulation No. 7 of 2010 on RTH Planning in every District of Semarang City. Since the regulation went into force, there has not been any evaluation of the suitability of the green space conditions in Mijen District against the established plans. SPOT-7 imagery, a high-resolution satellite image, can be used to map the condition of green open space in Mijen District using on-screen digitization techniques. A horizontal accuracy test of the SPOT-7 image was done to ensure the quality of the digitized data. Based on the digitized data, spatial analysis can be done to assess the suitability of the established plan. The horizontal accuracy test shows the CE90 value of 1,829, indicating that the data is classified as class 2 on a scale of 1:5,000. Then based on the 18 types of green open space plans in Mijen District, there are 8 types of suitable green open space and 10 types of unsuitable green open space. However, the total area of the Mijen Subdistrict green space has fulfilled the total expected area in the Regional Regulation.